Trinity of sin : the wages of sin - DeMatteis, J. M.; Guichet, Yvel; Gorder, Jason; Eltaeb, Gabe; Mangual, Carlos M.; Esposito, Taylor; Lanham, Travis; Sienty, Dezi; March, Guillem, 1979-; Morey, Tomeu (New York : DC Comics, 2015)
"Pandora, The Phantom Stranger and The Question have hated each other for centuries...and nothing has changed! Now the Trinity of Sin are forced to work together to save humanity and uncover the darkest secrets of the universe in this new collection. Collects TRINITY OF SIN #1-6"--
Keywords: COMICS & GRAPHIC NOVELS / Superheroes; Graphic novels; Superhero comic books, strips, etc